An Empirical Study Of The Mediation Effect Of Online Shopping Decision Making Ability Between Cognitive Factors And Online Shopping Behaviour Of Indian Consumers (Journal of Namibian Studies : History Politics Culture, 2022)
This study aims to empirically identify the mediation effect (direct, indirect, and total effect) of Online Shopping Decision Making Ability (OSDMA) Between Cognitive Factors (CF) and Online Shopping Behavior (OSB) of Indian Consumers. An empirical approach using structural equation modeling (SEM) was performed to describe the linear and nonlinear relationships in the proposed model of the Online Shopping Decision Making Ability, Cognitive Factors and Shopping Behavior of Indian Online Consumers. The empirical results reveal that there is a considerable relationship between Cognitive Factors (CF) and Online Shopping Behavior (OSB). The Cognitive Factors (CF) has a significant effect on Online Shopping Decision Making Ability (OSDMA). There is a considerable relationship between Online Shopping Decision Making Ability (OSDMA) and Online Shopping Behavior (OSB). It is also found that Online Shopping Decision Making Ability (OSDMA) has no mediation in between Cognitive Factors (CF) and Online Shopping Behavior (OSB), therefore the Online Shopping Decision Making Ability does not mediate between Cognitive Factors and Online Shopping Behavior.